The Middle East and North Africa : A New Social Contract for Development - Zoellick, Robert B. (World Bank, Washington, DC, 2018)
Robert B. Zoellick, President of the World Bank Group, discussed the political firestorm that engulfed Tunisia and the wider Middle East and its lessons for a new social contract for development that goes beyond the region itself. He argued for modernizing multilateralism in the Arab World, reforming international institutions to reflect power shifts in the world. Development economics must be democratized. Investment in the Arab World needs to be more diversified, while the governments increase accountability and reduce corruption and conflict. The new Arab voices are calling for dignity and respect and a series of changes amounting to a new social contract. While the World Bank once steered away from political topics, today our shareholders know that corruption is a drag on economies, strangling opportunity and taxing the poor. Now, anticorruption, gender, and transparency are vital to the practices of the World Bank Group. The upcoming new World Development Report stresses the role of legitimate institutions and governance. Citizen participation matters. Zoellick discussed job creation and safety nets as keys to maintaining development momentum in the region.